2005
DOI: 10.1007/s10384-004-0150-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of ischemia–Reperfusion injury by optical coherence tomography in the rat retina

Abstract: OCT can detect retinal changes quantitatively after ischemia-reperfusion injury, and the retinal thicknesses obtained from OCT images are probably a better measure of the true retinal thickness than those measured on histological sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
5
9
0
Order By: Relevance
“…The reperfusion injury in a case of CRAO is being reported for the first time in human and corroborates well with the study on a rat model where similar findings were observed on day 4 and 7, respectively 5. Timeline of reperfusion injury in CRAO gives us a novel insight into the critical period for treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The reperfusion injury in a case of CRAO is being reported for the first time in human and corroborates well with the study on a rat model where similar findings were observed on day 4 and 7, respectively 5. Timeline of reperfusion injury in CRAO gives us a novel insight into the critical period for treatment.…”
Section: Discussionsupporting
confidence: 88%
“…MEMRI-derived thickness of the entire neural retina (≈235 μm), excluding the choroidal vascular layer, is in good agreement with the total thickness of the rat neural retina reported using histology (24,25), ultrasound (26), and optical coherence tomography (27,28). Importantly, thicknesses of individual layers determined by our histology are also in general agreement with those reported by histology (24) and ultrasound (26).…”
Section: Discussionsupporting
confidence: 81%
“…This technique is infrequently used in rodent studies due to the technical challenges presented by small rodent eyes. However, when successfully applied in animal models, OCT is an extremely valuable tool as it measures retinal thickness (Fukuchi et al, 2001; Horio et al, 2001; Sho et al, 2005), the critical consequence of excessive vascular permeability and a frequently used endpoint in clinical trials.…”
Section: Discussionmentioning
confidence: 99%